Shift in dominant genotypes of Japanese encephalitis virus and its impact on current vaccination strategies - Xia, Qiqi; Yang, Yang; Zhang, Yan; Zhou, Lujia; Ma, Xiaochun; Xiao, Changguang; Zhang, Junjie; Li, Zongjie; Liu, Ke; Li, Beibei; Shao, Donghua; Qiu, Yafeng; et al. (Frontiers in Microbiology, 2023)
Japanese encephalitis (JE) is a zoonotic disease caused by the Japanese encephalitis virus (JEV), which is mainly transmitted in nature through mosquito bites. JEV can cause central nervous system damage in humans and reproductive disorders in pigs, posing a serious threat to public health. JEV is a flavivirus, classified into a single serotype with five genetically distinct genotypes (I, II, III, IV, and V). JEV genotype (G) III (GIII) had been the most dominant strain and caused numerous outbreaks in the JEV-endemic countries until 1990. However, in recent years, there have been some new changes in the epidemic of JE, including the expansion of the epidemic area and the displacement of dominant genotypes. Owing to the differences in the adaptability of the JEV in birds, the dominant genotype of the virus has gradually changed from GIII to GI. Between 2021 and 2022, Australia experienced an outbreak of viral encephalitis caused by GIV JEV infection. This is the first outbreak of human viral encephalitis caused by GIV JEV since it was first isolated in Indonesia in the late 1970s. In addition, after a lapse of 50 years, GV JEV has been detected and isolated in Culex mosquitoes in China and South Korea. It can be seen that GIV and GV JEV epidemic areas may be increasing, which seriously threatens the public safety of human beings and the healthy development of animal husbandry. Currently, the prevention and control of JE worldwide is mainly based on vaccination with the GIII strain vaccine. However, studies have shown that the antibodies induced by the GIII strain vaccine have a low neutralization ability to the GI and GV strains, and cannot completely protect animals from the GI and GV strains of JEV infection. The transformation of the dominant genotype of JEV and the expansion of the epidemic range has brought new challenges to the prevention and control of JE. This study reviewed the new characteristics of the epidemic of JE in recent years and the challenges it brings to prevention and control.